13th IEEE International Conference on BioInformatics and BioEngineering 2013
DOI: 10.1109/bibe.2013.6701687
|View full text |Cite
|
Sign up to set email alerts
|

LBP-based ear recognition

Abstract: The ear, as a biometric, has been given less attention, compared to other biometrics such as fingerprint, face and iris. Since it is a relatively new biometric, no commercial applications involving ear recognition are available. Intensive research in this field is thus required to determine the feasibility of this biometric. In medical field, especially in case of accidents and death, where face of patients cannot be recognized, the use of ear can be helpful. In this work, yet another method of recognizing peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In this work, we use deep CNN for ear feature extraction. Instead of deep features, many hand-crafted features, including both holistic [27] and local [7,[28][29][30] ones, have been suggested for ear images. Compared with hand-crafted features, deep CNN features are learned in a data-driven manner, and have proven its effectiveness in many vision tasks.…”
Section: Ear Feature Extractionmentioning
confidence: 99%
“…In this work, we use deep CNN for ear feature extraction. Instead of deep features, many hand-crafted features, including both holistic [27] and local [7,[28][29][30] ones, have been suggested for ear images. Compared with hand-crafted features, deep CNN features are learned in a data-driven manner, and have proven its effectiveness in many vision tasks.…”
Section: Ear Feature Extractionmentioning
confidence: 99%
“…For the appearance-based features, it mainly includes intensity, directional and spatial-temporal information. Many of works have presented holistical features such as Eigenear and Eigenface [2], ICA [13], active shape model to detect outer ear contour [14], 1 D and 2 D Gabor filter [15,16], and locale features such as LBP [17], HOG [18], kernel of polar sine transform (PST) [19], SIFT [20], and SURF [21]. Recently, Nanni and Lumini [22] adopted the sequential forward floating selection (SFFS) to select the best features from sub-windows in an ear image.…”
Section: Ear Recognitionmentioning
confidence: 99%
“…2D approaches are more appropriate for our domain because of the field requirements of fast and cheap solutions. Extracting a feature vector from a 2D ear representation has been done in many ways including Eigen Ears (PCA) [Chang et al, 2003], Force Field [Abdel- Mottaleb and Zhou, 2005], GFD [Abate et al, 2006], SIFT/SURF [Cummings et al, 2010, Kisku et al, 2009, and LBPs [Wang et al, 2008, Boodoo-Jahangeer andBaichoo, 2013].…”
Section: Related Workmentioning
confidence: 99%
“…LBPs [Ojala et al, 1996] demonstrated good performance in ear biometrics [Wang et al, 2008, Boodoo-Jahangeer andBaichoo, 2013]. Following [Takala et al, 2005, Wang et al, 2008 we use P sampling points on a circular grid of radius R, and uniform binary patterns u2 originally introduced by [Mäenpää et al, 2000] (LBP u2 (P,R) ).…”
Section: Local Binary Patternsmentioning
confidence: 99%